2019
DOI: 10.1093/mnras/stz1517
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mass-Ratio Distribution of Spectroscopic Binaries. II. The Boundaries of the Brown-Dwarf Desert as Seen with the APOGEE Spectroscopic Binaries

Abstract: Analysis of APOGEE DR12 stellar radial-velocities by Troup et al. (2016) affirmed the existence of the well-known Brown-Dwarf Desert (BDD). They detected a dearth of spectroscopic binaries (SB) with periods shorter than ∼ 10-30 days and secondaries with masses in the range of ∼ 0.01-0.1 M . We reconsider here their sample of binaries, focusing on 116 systems on the main sequence of the Gaia color-magnitude diagram, with mostly K-dwarf primaries. Using our recently devised algorithm to analyze the mass-ratio di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…M-type (Dieterich et al 2012;Duchêne & Kraus 2013), solar-type (Grether & Lineweaver 2006;Santerne et al 2016), and A-type (Murphy et al 2018) primaries all exhibit an intrinsic dearth of close brown dwarf companions (M2 0.08 M⊙) commonly known as the brown dwarf desert. The brown dwarf desert is observed within a 1 au (Grether & Lineweaver 2006;Csizmadia et al 2015;Santerne et al 2016;Murphy et al 2018;Shahaf & Mazeh 2019), and only ≈ 2% of stars have brown dwarf companions across intermediate separations of a ≈ 10 -100 au (Kraus et al 2008(Kraus et al , 2011Dieterich et al 2012;Wagner et al 2019;Nielsen et al 2019). Even if brown dwarf companions are capable of suppressing planet formation, their contribution is statistically insignificant compared to close stellar companions.…”
Section: Impact Of Close Binaries On Planet Occurrence Ratesmentioning
confidence: 99%
“…M-type (Dieterich et al 2012;Duchêne & Kraus 2013), solar-type (Grether & Lineweaver 2006;Santerne et al 2016), and A-type (Murphy et al 2018) primaries all exhibit an intrinsic dearth of close brown dwarf companions (M2 0.08 M⊙) commonly known as the brown dwarf desert. The brown dwarf desert is observed within a 1 au (Grether & Lineweaver 2006;Csizmadia et al 2015;Santerne et al 2016;Murphy et al 2018;Shahaf & Mazeh 2019), and only ≈ 2% of stars have brown dwarf companions across intermediate separations of a ≈ 10 -100 au (Kraus et al 2008(Kraus et al , 2011Dieterich et al 2012;Wagner et al 2019;Nielsen et al 2019). Even if brown dwarf companions are capable of suppressing planet formation, their contribution is statistically insignificant compared to close stellar companions.…”
Section: Impact Of Close Binaries On Planet Occurrence Ratesmentioning
confidence: 99%
“…Binaries that formed early have, on average, migrated to shorter periods and have larger q. Various surveys have demonstrated that solar-type primaries exhibit a dearth of close brown dwarf companions within P 100 days, commonly known as the brown dwarf desert, but that the frequency of brown dwarf companions increases with increasing separation (Grether & Lineweaver 2006;Kraus et al 2008Kraus et al , 2011Csizmadia et al 2015;Wagner et al 2019;Shahaf & Mazeh 2019). Our model naturally reproduces the brown dwarf desert, as it is very difficult for very low-mass companions to migrate within P 100 days without also accreting above M2 > 0.08 M⊙.…”
Section: Solar-mass Binariesmentioning
confidence: 99%
“…Recently, more and more BDs have been found to reside in this desert (e.g., Persson et al 2019;Carmichael et al 2019Carmichael et al , 2020Acton et al 2021). As suggested by Shahaf & Mazeh (2019), characterization of the shape of the brown dwarf desert in the period-mass diagram by a large sample of circumstellar BDs can improve our understanding of its origin.…”
mentioning
confidence: 94%